COMPARISON OF SAFETY AND EFFICACY OF RIVAROXABAN AND ENOXAPARIN FOR TREATMENT OF CANCER ASSOCIATED VENOUS THROMBOEMBOLISM - KHAN , RAA; MASOOD , AI; SAFDAR, A; MANAN , A (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in Nishtar Medical Hospital from January 2022 to January 2023 to compare the safety and efficacy of Rivaroxaban with low molecular weight heparin (LMWH) such as enoxaparin for the treatment of cancer-associated venous thromboembolism (VTE). A total of 250 patients were included in the study. The participants were divided into a control group (who received LMWH (enoxaparin)) and a study group (who received Rivaroxaban). The primary outcome was the occurrence of symptomatic VTE and major bleeding events during the follow-up period. After 3 months, VTE recurred in 1 (1.6%) patient in the rivaroxaban group and 6 (3.1%) patients in the enoxaparin group. After 3 months, Rivaroxaban had 4 (6.6%), and the enoxaparin group had 5 (2.6%) major bleeding events. During the 3 to 12-month period, there was no significant difference regarding treatment outcomes in groups. Based on the results, we can conclude from this study that Rivaroxaban offers effective therapy for cancer-associated VTE, but its bleeding complications are higher than LMWH.